Meso Hybridized Silk Fibroin Watchband for Wearable Biopotential Sensing and AI Gesture Signaling - Xiao Wang; Changsheng Lu; Zerong Jiang; Guangwei Shao; Jingzhe Cao; Xiang Yang Liu (Advanced Science)
Abstract Human biopotential signals, such as electrocardiography, are closely linked to health and chronic conditions. Electromyography, corresponds to muscle actions and is pertinent to human‐machine interactions. Here, we present a type of smart and flexible watchband that includes a mini flexible electrode array based on Mo‐Au filament mesh, combined with mesoscopic hybridized silk fibroin films. As the layer in contact with the skin, waterborne polyurethane and SF create a highly flexible and permeable meso‐hybridized SF/WPU layer, ensuring skin‐friendliness and comfortable wearing. The flexible FM electrodes are created by integrating Mo‐Au FM into 2D‐interconnected networks. Molybdenum filaments provide high rigidity and are coated with Aurum to enhance conductivity. The use of Mo‐Au FMs in warp‐knitted patterns results in high SNR (43.22 dB), high sensitivity (44.43 mV/kg), and significant motion noise reduction due to the pattern's elastic deformability and skin‐gripping properties. Leveraging these unique technologies, these smart watchbands excel in prolonged sensing operation, grasping force detection, and gesture recognition. Through smart raining via deep learning, we achieved an unparalleled recognition rate (96% across 20 volunteers of different genders) among other EMG sensing devices. These results have significant implications for human‐machine interaction, including applications in underwater robot control, drone operation, and autonomous vehicle control.